Boundaries of Samudaripen: Representations of the Romani Holocaust in Croatian and Serbian literature - Giergiel, Sabina; Taczyńska, Katarzyna (Poznańskie Studia Slawistyczne, 2025)
The aim of this article is to analyse the relatively unknown literary representations of the Romani Holocaust within Croatian and Serbian cultures (both in personal documents and works of fiction). Mentions of Samudaripen in Croatian autobiographical texts are episodic and secondary to other stories, and they hardly ever come up in Croatian works of fiction. In Serbian literary works, there are two main modes of referencing Samudaripen: 1) by evoking it, usually in the context of the Jewish Holocaust, as a historically documented fact or 2) by presenting it as a novel’s main theme or one of its equally significant plotlines; it is, however, rarely a historically and culturally embedded narrative and more ambitious literary work, which results in its limited impact.